Post-1989 Cold War Diplomatic Shifts in Southern Africa - Scarnecchia, Timothy (Comparativ, 2019)
This article evaluates new materials from British and US-American archives that have now become accessible and concern diplomatic negotiations on the end of the conflicts in Namibia, Angola and Mozambique as well as the end of apartheid in South Africa. Older interpretations that view the withdrawal of the Soviet Union as a betrayal of the old allies within the communist and liberation movements in southern Africa are supplemented by a more nuanced view that locates the beginning of this change in 1988 and in the negotiations over the withdrawal of Cuban troops from Angola and Namibian independence. The aim of Soviet foreign policy was no longer to give unconditional support to its allies, but rather to calm and stabilise the political situation in order to help the new world order that was seeking to break through. As a result, a democratic government for South Africa, supported by a majority vote of the electorate, also moved into the focus of Soviet policy, which in turn reduced fears on the US side of a socialist one-party system. From the consulted British and US sources it can also be seen that in a complicated process of rapprochement, the Soviet negotiators developed sympathies for capitalist development in South Africa and also saw opportunities emerging for their own country.